2017
DOI: 10.5056/jnm17067
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Corticotropin-releasing Hormone Administration Increases Esophageal Electrical Sensitivity in Healthy Individuals

Abstract: Background/AimsWhen a person is experiencing stress, corticotropin-releasing hormone (CRH) can modulate gut physiologies, such as visceral sensation or gastrointestinal motility, and its intravenous administration mimics stress-induced physiological changes. However, the influence of CRH on the esophagus is yet unknown. Accordingly, we investigated whether intravenous CRH administration increases esophageal sensitivity to electrical stimulation in healthy Japanese subjects. MethodsTwenty healthy subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Moreover, CRH plays a key role in activating the HPA axis for endocrine regulation. Yamasaki et al [ 35 ] demonstrated that esophageal sensitivity increases after the intravenous injection of CRH in a normal population, indirectly emphasizing the importance of psychological stress in esophageal VH. Brain-gut peptides, which can regulate visceral sensation, gastrointestinal motility, and mental psychology, are small molecular substances distributed within the brain and the intestines.…”
Section: Nerd and Abnormal Psychological Factorsmentioning
confidence: 99%
“…Moreover, CRH plays a key role in activating the HPA axis for endocrine regulation. Yamasaki et al [ 35 ] demonstrated that esophageal sensitivity increases after the intravenous injection of CRH in a normal population, indirectly emphasizing the importance of psychological stress in esophageal VH. Brain-gut peptides, which can regulate visceral sensation, gastrointestinal motility, and mental psychology, are small molecular substances distributed within the brain and the intestines.…”
Section: Nerd and Abnormal Psychological Factorsmentioning
confidence: 99%
“…T. Yamasaki и соавт. [42] продемонстрировали, что чувствительность пищевода в нормальной популяции повышалась после внутривенного введения кортикотропин-рилизинг-гормона, что косвенно подчеркивает влияние психологического стресса на развитие висцеральной гиперчувствительности пищевода.…”
Section: Reviewunclassified